DAMPAK PENGEMBANGAN INDUSTRI PENGOLAHAN IKAN TERI TERHADAP KONDISI SOSIAL EKONOMI MASYARAKAT (STUDI KASUS : PULAU PASARAN) - Anjani, Prita; Setianingrum, Lutfi; Putri, Marsista Buana (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
In an effort to develop an anchovy processing industry on Pasaran Island in order to increase the selling value and quality of the processed products, in 2003 the community began to change the fish processing system. The development of this processing industry will certainly have an impact on the socio-economic conditions of the community. This study aims to identify the impact of the development of anchovy processing industry in Pasaran Island on the socio-economic conditions of the community. In responding to this research, quantitative analysis was used to see changes in the socio-economic conditions of the community before and after the development of the fish processing industry. Qualitative descriptive analysis to describe the impact and spatial linkages of Pasaran Island anchovy processing activities on the socio-economic. From the results of the analysis it was found that the development of the anchovy processing industry in Pasaran Island had an impact on the socio-economic conditions of the community. These impacts include changes in employment opportunities, housing conditions, infrastructure development, ownership of living facilities, income and expenses. The impact on employment opportunities such as opening jobs, especially women workers from outside the island. The impact on housing conditions such as the change of buildings from wooden houses to permanent houses. The impact on infrastructure development such as easy access to clean water, electricity and road conditions. The impact on ownership of living facilities such as an increase in the number of ownership of living facilities. Impact on income and expenses such as increased income and expenses. Furthermore, the spatial linkage of anchovy processing activities that agglomerate on Pasaran Island results in an even distribution of the socio-economic conditions of the community.